2012
DOI: 10.2503/jjshs1.81.198
|View full text |Cite
|
Sign up to set email alerts
|

Far-red Light Supplemented with Weak Red Light Promotes Flowering of Gypsophila paniculata

Abstract: A low red (R): far-red (FR) ratio is known to promote flowering of Arabidopsis and several long-day cut flowers, whereas not much information is available on the effects of single light qualities and their combinations on flowering. Therefore, the effects of light quality on the flowering of Gypsophila paniculata were investigated using light-emitting diodes (LEDs) emitting the following lights: FR, R, and blue (B). Flowering and flower budding were observed under long-day conditions with FR, while no flowerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…paniculata 'Million Star' (Sumika Agrotech, Osaka, Japan) and 'Bristol Fairy' (Japan Agribio Company, Tokyo, Japan) were grown under short-day conditions with an 8-h photoperiod for approximately 4 weeks. Thereafter, 16-h light treatment was started following the method of Nishidate et al (2012). Three lateral shoots of 'Million Star' plants with approximately 10 leaves were grown in a growth chamber at 22/18°C under natural light from 9:00 to 17:00 and under far-red or blue LEDs from 17:00 to 9:00 for observation of flowering, expression analysis of GpFT and GpSOC1, and sequencing of GpFKF1 and GpGI cDNAs.…”
Section: Plant Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…paniculata 'Million Star' (Sumika Agrotech, Osaka, Japan) and 'Bristol Fairy' (Japan Agribio Company, Tokyo, Japan) were grown under short-day conditions with an 8-h photoperiod for approximately 4 weeks. Thereafter, 16-h light treatment was started following the method of Nishidate et al (2012). Three lateral shoots of 'Million Star' plants with approximately 10 leaves were grown in a growth chamber at 22/18°C under natural light from 9:00 to 17:00 and under far-red or blue LEDs from 17:00 to 9:00 for observation of flowering, expression analysis of GpFT and GpSOC1, and sequencing of GpFKF1 and GpGI cDNAs.…”
Section: Plant Materialsmentioning
confidence: 99%
“…For example, a low red:far-red ratio maintained using films that change light quality in daytime and redor far-red-rich fluorescent lamps at night promote flowering in Matthiola incana (Yoshimura et al, 2002(Yoshimura et al, , 2006, and low and high red:far-red ratios promote and retard flowering under long-day conditions in Eustoma grandiflorum (Sato et al, 2009;Yamada et al, 2008aYamada et al, , b, 2009). Far-red alone and a low red:far-red ratio promote flowering under long-day conditions with LEDs in Gypsophila paniculata (Nishidate et al, 2012), and a low red:far-red ratio also promotes flowering in Campanula carpatica (Kristinsen, 1988). However, there are few studies on the flowering response to blue light in long-day cut flowers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The flowering behavior of Gypsophila paniculata is strongly influenced by growth conditions, mainly daylength and temperature (Thakur et al, 2013). It has been reported that plants will stay in the vegetative growth stage and form a rosette under short daylighting and lower temperatures (Nishidate et al, 2012). The formation of the rosette significantly affects the flower production of Gypsophila paniculata because these rosette plants cannot bloom.…”
mentioning
confidence: 99%
“…In LD plants, FR-deficient environments often delay flowering (Kim et al, 2000;van Haeringen et al, 1998), but providing photoperiodic lighting with only FR is not consistently effective at promoting flowering (Craig and Runkle, 2016;Nishidate et al, 2012). Therefore, a combination of R and FR radiation can be used for photoperiodic control of LD plants.…”
mentioning
confidence: 99%